TERMINOLOGIYANING NAZARIY MASALALARI (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article provides a comprehensive analysis of the concept of a term, its linguistic characteristics, and its role in the development of scientific thinking. It examines the historical formation of terms, their expansion in connection with scientific and technological progress, and their importance in creating a unified system of concepts within international cooperation. The study also substantiates, from a linguistic perspective, the special functional features, morphological stability, and precision requirements of terms used in various fields of science and technology. Furthermore, the research emphasizes that terminology, as an integral part of scientific discourse, is a dynamic phenomenon that reflects societal development.